2008
DOI: 10.1136/jmg.2008.058016
|View full text |Cite
|
Sign up to set email alerts
|

Complex and segmental uniparental disomy updated

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
112
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 146 publications
3
112
0
7
Order By: Relevance
“…Moreover, smaller UPD events are less likely to be pathogenic and are much more likely to be mosaic (Kotzot 2008), implying that alternative UPD detection approaches, based on B-allele frequency of proband genotypes, would be more appropriate for segmental UPD events. We implemented UPD detection on 1057 unique trios and identified four probands with whole-chromosomal isodisomy, one with whole-chromosomal heterodisomy, and one proband with segmental uniparental isodisomy of 10 Mb.…”
Section: à323mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, smaller UPD events are less likely to be pathogenic and are much more likely to be mosaic (Kotzot 2008), implying that alternative UPD detection approaches, based on B-allele frequency of proband genotypes, would be more appropriate for segmental UPD events. We implemented UPD detection on 1057 unique trios and identified four probands with whole-chromosomal isodisomy, one with whole-chromosomal heterodisomy, and one proband with segmental uniparental isodisomy of 10 Mb.…”
Section: à323mentioning
confidence: 99%
“…The UPD chromosome can be characterized in four ways: (1) extent: affecting the whole chromosome (complete) or a portion of the chromosome (segmental); (2) zygosity: affecting all cells (constitutive) or a proportion of cells (mosaic); (3) by homolog segregation: whether the centromeric regions are identical (isodisomy) or represent both grandparental homologs (heterodisomy); and (4) by parental-origin: maternal or paternal. The origin of UPD often entails meiotic nondisjunction followed by a mitotic rescue event, but the possibility of crossing-over of homologs and missegregation of translocated chromosomes and other complex events are possible (Kotzot 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This simultaneous occurrence of both abnormalities is particularly common when a marker chromosome, whole chromosome aneuploidy (often mosaic) or Robertsonian translocation, is observed. [4][5][6] It has been suggested that more than a third of cases of UPD are the likely outcome of or are associated with a chromosomal abnormality. 6 Therefore, the chromosomal contribution to UPD formation is a more common phenomenon than commonly perceived.…”
Section: Introductionmentioning
confidence: 99%
“…The recurrence risk for UPD and therefore the same recessive condition in a subsequent child in general is believed to be so low that invasive prenatal diagnosis is not generally indicated. 28 The parents of patient 1 are past reproductive age, however, the parents of patient 2 did opt for prenatal diagnosis for the c.533G4A (p.W178X) mutation in their next child. Considering that the patient appeared to have uniparental isodisomy due to non-disjunction in the maternal germline, and that the couple had another child with a 48,XXXY karyotype, also a chromosome abnormality consistent with non-disjunction in the mother, it may be that there are additional genetic factors in this family predisposing to such events.…”
Section: Discussionmentioning
confidence: 99%